Rodolpho Ortenblad Filho: estudo sobre as residências - Pereira, Sabrina Souza Bom (2010)
The architect Rodolpho Ortenblad Filho, soon after completing college of architecture at Mackenzie University, in 1950, had the opportunity to travel to the United States of America, motivated by the desire to know the "modern works , which until then he had only seen in magazines. The influence of this trip on his way to see architecture is noteworthy, and also being reflected in the design of his projects. So, it's no surprise that Ortenblad s projects were cited always though few in number and in a few times in scholarly works in contexts that relate to residential architectural production from Sao Paulo and the American modern home. This dissertation, entitled "Rodolpho Ortenblad Filho: estudo sobre as residências", is the first academic research topic focused exclusively on his work, what involve for greater intelligibility of his residential projects, which have received reviews that outline its main features the necessary submission of his personal background and an overview of completed projects involving concourses and projects for various programs: school, club, industry. Rodolpho Ortenblad Filho realized hundreds of projects between the years 1950 and 1984, many of them published in Acrópole magazine - from which he was director from 1953 to 1955, a period corresponding to editions 182 to 200. His work was noticed and respected in professional circles, as demonstrated by several current testimonials from colleagues of his generation and the publish of two of his homes in the Japanese magazine World's Contemporary Houses ((ed. 5), flanked by Casa de Vidro (The Glass House), by Lina Bo Bardi, Casa do Morumbi, by Oswaldo Bratke, Casa de Canoas, by Oscar Niemeyer, Casa Milton Guper, by Rino Levi, and houses of renowned architects from Argentina, Mexico and Uruguay.